2022
DOI: 10.1002/bse.2996
|View full text |Cite
|
Sign up to set email alerts
|

Jump‐starting, diffusing, and sustaining the circular economy

Abstract: Jump-starting, diffusing, and sustaining the circular economy 1 | INTRODUCTIONCircular economy, which we succinctly define as a zero-waste economic system, is often touted as a promising approach to decarbonize industrial processes and to limit global warming to 1.5 . Unsurprisingly, therefore, the circular economy has emerged as a central avenue in the corporate sustainability lexicon. Explicitly or implicitly, most major global companies adduce to the circular economy in their sustainability communications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In addition, the paper substantiates the fact that NRBV involves internal and external levels, as suggested in Martín‐de Castro et al (2016), and intraorganizational and interorganizational practices, as suggested by Shi et al (2012). Our results confirm that dynamic capabilities are key to promoting the CE, as they stimulate firms' engagement with stakeholders (Panwar & Niesten, 2022). In line with Karagouni and Protogerou (2015), the development of dynamic capabilities facilitates value co‐creation processes, or rather, these processes are the result of dynamic capabilities.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In addition, the paper substantiates the fact that NRBV involves internal and external levels, as suggested in Martín‐de Castro et al (2016), and intraorganizational and interorganizational practices, as suggested by Shi et al (2012). Our results confirm that dynamic capabilities are key to promoting the CE, as they stimulate firms' engagement with stakeholders (Panwar & Niesten, 2022). In line with Karagouni and Protogerou (2015), the development of dynamic capabilities facilitates value co‐creation processes, or rather, these processes are the result of dynamic capabilities.…”
Section: Discussionsupporting
confidence: 80%
“…The development or adoption of clean technologies, as well as circularity-oriented practices, should be encouraged by policy makers through adequate policies and funding. Lastly, in line with Panwar and Niesten's (2022) assertion, jump-starting the circular economy at the exemplar firms' level favors the adoption of CE practices and develops dynamic capabilities at the "group efforts" level, by cultivating an ecosystem approach, also by encouraging the coevolution between borncircular and growing-circular firms. Local and regional institutions should contribute identifying new trajectories in CE, mobilizing resources and consensus, and incentivizing them (Bressanelli et al, 2022).…”
Section: Product Stewardship (Ps)-reconfiguring (Re)mentioning
confidence: 67%
See 2 more Smart Citations
“…There are many levers which may block, enable or even drive a transition towards circularity. These levers will be critical to institutionalizing circularity, by jumpstarting, diffusing and then sustaining circular economy (Panwar & Niesten, 2022). We have used the term ‘lever’ because these are neither fixed nor immutable; we have also termed them levers because our findings show that these elements make a difference to the actions of multinational companies when they define their ambitions based upon the intersection of their corporate culture and values with the wider economic, legislative and cultural context in which they operate.…”
Section: Concluding Commentsmentioning
confidence: 99%